2019
DOI: 10.3389/fnut.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation and Seasonality on Circulating Cytokines in Adolescents: Analysis of Data From a Feasibility Trial in Mongolia

Abstract: Vitamin D deficiency is prevalent in human populations and has been linked to immune dysfunction. Here we explored the effects of cholecalciferol supplementation on circulating cytokines in severely vitamin D deficient [blood 25(OH)D << 30 nmol/L] adolescents aged 12–15 from Mongolia. The study included 28 children receiving 800 IU daily cholecalciferol for 6 months spanning winter and spring, and 30 children receiving placebo during the same period. The levels of 25(OH)D were assessed at baseline, 3 and 6 mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Studies have further shown VitD’s importance for protection against different infections [ 14 ] including respiratory tract infections [ 15 17 ]. VitD delivers such a protection through the regulation of the immune system via VitD receptors [ 18 ] and in this process it also reduces the production of pro-inflammatory cytokines [ 19 21 ]. Recent data have shown a strong correlation between excessive cytokine production and severity of COVID-19 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have further shown VitD’s importance for protection against different infections [ 14 ] including respiratory tract infections [ 15 17 ]. VitD delivers such a protection through the regulation of the immune system via VitD receptors [ 18 ] and in this process it also reduces the production of pro-inflammatory cytokines [ 19 21 ]. Recent data have shown a strong correlation between excessive cytokine production and severity of COVID-19 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work, we characterized the gut microbiome of adults with and without metabolic syndrome from Kazakhstan, a country in Central Asia ( 8 ). As part of our overarching objective to better understand the relationship between the mucosal and systemic correlates of chronic disease in this region ( 8 , 9 ), here we expand on our earlier findings and focus on the gut microenvironment in individuals with psoriasis. We hypothesized that psoriasis in adult Central Asians is associated with gut inflammation and microbiome alterations.…”
Section: Introductionmentioning
confidence: 99%
“…2e). A study of VitD supplementation in Mongolian children noted significant increases in serum IL-6 (as well as a non-significant increase in IL-10) 39 indicating that our observations can also occur in vivo. In the skin, the site of the highest levels of VitD, overexpression of IL-6 provides protection from injurious stimuli or infection 40 and IL-6 deficiency impairs cutaneous wound healing 41 .…”
mentioning
confidence: 58%